The Important Role of Volatile Components From a Traditional Chinese Medicine Dayuan-Yin Against the COVID-19 Pandemic - Zhang, Xiao-rui; Li, Ting-na; Ren, Yuan-yuan; Zeng, Yi-jia; Lv, Hong-yang; Wang, Jin; Huang, Qin-wan (Frontiers in Pharmacology, 2020)
Aromatic Chinese herbs have been used to prevent plague since ancient times, and traditional Chinese medicine has unique advantages in the prevention and treatment of epidemic disease. According to the traditional Chinese medicine treatment plan in the National COVID-19 Diagnosis and Treatment Plan (Trial Seventh Edition) of the National Health Commission, Chinese patent medicines or prescriptions containing more aromatic Chinese herbs are selected for prevention and treatment during the period of medical observation, clinical treatment, and recovery of confirmed patients. Some local health committees or traditional Chinese medicine administrations recommend a variety of other ways to use aromatic traditional Chinese herbs (external fumigation, moxibustion, wearing sachet, etc.) to prevent and cure COVID-19. The efficacy of aromatic Chinese herbs plays a decisive role in the prevention and treatment of COVID-19. The unique properties, chemical composition, and action mechanism of aromatic Chinese herbs are worthy of extensive and in-depth experimental and clinical research, which can provide a reference for the follow-up treatment of novel coronavirus and the development of corresponding drugs. Dayuan-yin, in 2003, the treatment of the SARS virus, produced excellent results. Individually, 112 confirmed cases were administered with this drug between January and April 2003, with more than 93.7% of patients showing noticeable improvement in symptoms and being cured. In the process of treating COVID-19, Dayuan-Yin also showed an excellent curative effect and was selected as one of the nationally recommended prescriptions. Based on the nationally recommended prescription named Dayuan-Yin, this review discusses the role of volatile components in the prevention and treatment of COVID-19, and speculates the possible mechanism of its role, to provide the basis for the prevention and treatment of COVID-19.